The Validity and Reliability of Six Minute Walk Test in a 15 Meter Track - Nury Nusdwinuringtyas; Kevin Triangto; Idrus Alwi; Faisal Yunus (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
ABSTRACTIntroduction: Endurance is one of the key fitness measure that should be evaluated daily. Clinicalassessment of endurance in daily practice is usually hurdled by limitation of hospital spaces. Anotherobstacle arise that shorter six-minute walk test (6MWT) track will lead to more turning motion, yieldingshorter straight walking distance with increased ener gy expenditure.Methods: This cross sectional study compares 6MWT on a 15 meter corridor, to the gold standardBiodex® gait trainer for healthy adults aged 18-50 years. Subjects without any anatomical abnormalitiesor systemic disorders were recruited, and instructed to turn in a three-step method at track ends tomaximize walking distance. Furthermore, validity and reliability assessments to obtain both Pearsoncorrelation and Cronbach Alpha values were performed respectively.Results: Among 123 subjects, 58 males aged ranging from 18 to 45 years, and females between 18 to42 years were recruited. Anthropometrical values were similar between gender. Significant differencein walking distance and walking speed was observed. Comparison of walking distance between the twomodalities were seen to be statistically similar (p=0.693). Pearson validity test was proven significant (p<0.001) with a correlation coefficient of r = 0.998, while reliability test obtained Cronbach’s Alpha valueof 0.999, hence showing that these are both valid and reliable.Conclusion: Good validity and reliability of 6MWT in 15 meter track as compared to the gold standardBiodex® gait trainer was demonstrated in this study. Moreover, shorter track is a potential modificationadhering to the limitation of operational space. The three-step turning method could significantlyimproves total walk distance, and thus is suggested.Keywords: clinical assessment, endurance, six-minute walk test, walk dist ance, walking speed